Analysis of Cooling Curves of Nodular Cast Iron - Bartošová, Marianna; Pribulova, Alena; Eperješi, Štefan; Futáš, Peter (Journal of Casting & Materials Engineering, 2018)
The solidification of cast iron is a complex process with characterized entrance and marginal conditions. Thermal analysis is one of the processes that allows us to observe the solidification of alloys. There is a possibility of gaining information about the melted cast iron quality and predicting the final properties of the cast by evaluating the scanned cooling curves by solidification (stable and metastable system). This article deals with the study and analysis of cooling curves taken from production conditions of a foundry during ductile cast iron production. The aim is to discover the reproduction and reliability of the thermal analysis results of cast iron. The study of the progress of the cooling curves and their first derivation to follow the reactions of the curves to changing factors in the production process.